Bedside - Segar, Nora (The Hastings Center report, 2013)
Mrs. Vogul wore the same zip-up white fleece and leather sandals for thirty-one days of her husband's hospitalization. She slept in the empty bed in his two-person room or in a chair. When she couldn't sleep, she stood motionless in the hallway like a gargoyle protecting his room. During each crisis, Mrs. Vogul frowned in the doorway, telling us which tests to order and which interventions we were allowed to try. When we supported his breathing with an oxygen mask, she took it off. “Don't try to put that mask back on him again!” she warned as he gasped for air. Despite this, Mr. Vogul was “full code.” If he were to stop breathing on his own, she wanted us to intubate him. If his heart were to stop, she wanted us to try to restart it. With no advance directive to guide us, we deferred these decisions to Mrs. Vogul, despite what sometimes seemed like contradictions in what she wanted for her husband.